2017
DOI: 10.1002/jbmr.3162
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide Is Ineffective in Treating Tumor-Induced Osteomalacia: Results of a Short-Term Therapy

Abstract: Tumor-induced osteomalacia (TIO) is a rare paraneoplastic syndrome in which unregulated hypersecretion of fibroblast growth factor 23 (FGF23) by phosphaturic mesenchymal tumors (PMT) causes renal phosphate wasting, hypophosphatemia, and osteomalacia. The resulting mineral homeostasis abnormalities and skeletal manifestations can be reversed with surgical resection of the tumor. Unfortunately, PMTs are often difficult to locate, and medical treatment with oral phosphate and vitamin D analogues is either insuffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Since SUV max is a surrogate marker of SSTR expression (42), it may be inferred that signal transduction via somatostatin receptors is possibly not involved in the regulation of FGF23 secretion by the tumor tissue. As firm evidence to our hypothesis is the fact that octreotide, a somatostatin receptor ligand, is largely ineffective in correcting the biochemical abnormalities in TIO (43, 44, 45).…”
Section: Discussionsupporting
confidence: 65%
“…Since SUV max is a surrogate marker of SSTR expression (42), it may be inferred that signal transduction via somatostatin receptors is possibly not involved in the regulation of FGF23 secretion by the tumor tissue. As firm evidence to our hypothesis is the fact that octreotide, a somatostatin receptor ligand, is largely ineffective in correcting the biochemical abnormalities in TIO (43, 44, 45).…”
Section: Discussionsupporting
confidence: 65%
“…Seufert et al reported a patient with left thigh TIO localized on octreotide scinitigraphy having complete resolution of phosphaturia and normalization of serum phosphorus with 50–100 µg of octreotide thrice a day in preoperative setting (125). However, this initial success has not been replicated in subsequent studies (34, 126). Extrapolating from patients with hypoparathyroidism with elevated FGF-23 and serum phosphorus levels, Gellers et al advocated for the use of cinacalcet in the treatment of TIO (127).…”
Section: Treatmentmentioning
confidence: 95%
“…The basic regimen for TIO includes phosphate and active vitamin D (calcitriol and alfacalcidol) supplements [ 30 ] Side effects include nephrolithiasis, nephrocalcinosis, impaired renal function, and either secondary or tertiary hyperparathyroidism [ 29 ], necessitating close surveillance. Somatostatin receptor analogues have been used with some success [ 29 , 31 33 ]. Inconsistent results are reported regarding the efficacy of somatostatin receptor-based therapy with octreotide in this setting [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%